A Case of Acute Generalized Pustular Psoriasis of von Zumbusch Triggered by Hypocalcemia - Carlos Antônio Gusmão Guerreiro de Moura; Luiz Henrique de Assis; Paulo Góes; Fabiana Rosa; Victor Nunes; Ítalo Magalhães Gusmão; Constança Margarida Sampaio Cruz (Karger Publishers, 2015)
Psoriasis is an autoimmune disease triggered by different conditions in genetically susceptible people. It is characterized by variable cutaneous manifestations including localized or disseminated pustules. Generalized pustular psoriasis (GPP) has two main clinical forms: von Zumbusch psoriasis, characterized by severe erythrodermia and scaling skin after the resolution of pustules, and the annular form. GPP may also present severe extracutaneous manifestations including pneumonitis, heart failure and hepatitis. Old reports showed a relationship between hypoparathyroidism and hypocalcemia as triggers for GPP highlighting the importance of adequate workup of the patient and possible therapeutic changes in acute situations. Here, we present a case of severe von Zumbusch psoriasis with life-threatening complications triggered by severe hypocalcemia secondary to hypoparathyroidism successfully treated with aggressive calcium reposition.